Information and Communication Technologies in hybrid environments - Suárez Conejero , Juana Elvira (2022)
This article discusses the importance of ICTs in education based on their use in the teaching-learning process, recognizing that historically they have been applied for the benefit or detriment of humanity. It analyzes the production of information and knowledge in today's societies, from the perspective of non-professional informants found in virtual networks, as well as the responsibility of the academy in the generation of knowledge. It is recognized that, as consumers, we have a lack of skills to be able to choose the best information among all the possibilities presented in the network; in this problem also emerges the Dunning-Kruger syndrome that forces us to evaluate our competences before judging or prejudging a subject or discipline of knowledge. A call is made to address Educommunication as a strategy for the promotion of generational dialogue, between teachers and students, in hybrid environments, since classrooms are in a crucial historical moment where the indiscriminate consumption of information available in different spaces of the network can be vindicated. Likewise, experiences in teaching that reveal opportunities to improve academic spaces with the use of ICT are presented.